2011
DOI: 10.1186/1472-6785-11-22
|View full text |Cite
|
Sign up to set email alerts
|

Incongruence between morphotypes and genetically delimited species in the coral genus Stylophora: phenotypic plasticity, morphological convergence, morphological stasis or interspecific hybridization?

Abstract: BackgroundMorphological data suggest that, unlike most other groups of marine organisms, scleractinian corals of the genus Stylophora are more diverse in the western Indian Ocean and in the Red Sea than in the central Indo-Pacific. However, the morphology of corals is often a poor predictor of their actual biodiversity: hence, we conducted a genetic survey of Stylophora corals collected in Madagascar, Okinawa, the Philippines and New Caledonia in an attempt to find out the true number of species in these vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 50 publications
3
70
2
2
Order By: Relevance
“…Direct sequencing and subsequent phase analysis in a Bayesian framework revealed that all analyzed samples host either one or two dominant types of ITS region sequences, a situation previously reported in other coral genera (Flot et al, 2006(Flot et al, , 2008a(Flot et al, , 2011Schmidt-Roach et al, 2012). Moreover, most ITS region types that cooccurred in some Goniopora colonies were found to be harbored alone in other specimens, suggesting that these variants might be allelic and each samples might be either homogeneous or heterogeneous for this molecular locus (Flot et al, 2006(Flot et al, , 2011 as observed for single-copy nuclear genes such as ATPsβ and CalM.…”
Section: Alignment Statistics and Haplotype Determinationsupporting
confidence: 62%
See 2 more Smart Citations
“…Direct sequencing and subsequent phase analysis in a Bayesian framework revealed that all analyzed samples host either one or two dominant types of ITS region sequences, a situation previously reported in other coral genera (Flot et al, 2006(Flot et al, , 2008a(Flot et al, , 2011Schmidt-Roach et al, 2012). Moreover, most ITS region types that cooccurred in some Goniopora colonies were found to be harbored alone in other specimens, suggesting that these variants might be allelic and each samples might be either homogeneous or heterogeneous for this molecular locus (Flot et al, 2006(Flot et al, , 2011 as observed for single-copy nuclear genes such as ATPsβ and CalM.…”
Section: Alignment Statistics and Haplotype Determinationsupporting
confidence: 62%
“…Unfortunately, scleractinian morphology exhibits extensive phenotypic plasticity, high variability, and/or evolutionary convergence that often obscure natural patterns of evolution (e.g., Gittenberger and Hoeksema, 2006;Fukami et al, 2004;Todd, 2008;Flot et al, 2011;Budd et al, 2012). The integration of molecular tools with morphological analyses has proven to be powerful in clarifying misleading and complex phylogenies, with recent examples in the genera Pocillopora (Schmidt Roach et al, 2014), Psammocora (Stefani et al, 2008;Benzoni et al, 2010), and Desmophyllium (Addamo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pocillopora damicornis sensu lato morphological variants identified here are clearly associated with genetically distinct lineages, thus reinforcing the growing literature revealing cryptic speciation in a wide variety of coral groups and within so-called morphologically variable taxa, for example, Montipora spp. (Stobart and Benzie 1994), Montastraea annularis (Medina et al 1999), species within the Faviidae (Nunes et al 2008), and species within the Poritidae (Forsman et al 2009;Flot et al 2011). It should be noted, however, that while our results demonstrate that accepted ecomorphs of P. damicornis may represent different species, we do not completely discount the influence of eco-phenotypic variation in pocilloporid diversity and systematics.…”
Section: Phenotypic Plasticity Versus Genotypic Variation In P Damiccontrasting
confidence: 51%
“…A GTR substitution model was used with a 6 gamma categories and Stylophora sp. as outgroup with ITS2 and ORF sequences from the specimen 04Oki195 (JN559077 and JN558888, Flot et al, 2011). In addition the 6 Seriatopora sequences from Nakajima et al (2017) were included in the ORF tree for comparison.…”
Section: Genetic Analyses Of the Coral Hostmentioning
confidence: 99%